Michael-type addition of azoles of broad-scale acidity to methyl acrylate - Boncel, Sławomir; Saletra, Kinga; Hefczyc, Barbara; Walczak, Krzysztof Z. (Beilstein Journal of Organic Chemistry, 2011)
An optimisation of Michael-type addition of azole derivatives of broad-scale acidity – ranging from 5.20 to 15.00 pKa units – namely 4-nitropyrazole, 3,5-dimethyl-4-nitropyrazole, 4(5)-nitroimidazole, 4,5-diphenylimidazole, 4,5-dicyanoimidazole, 2-methyl-4(5)-nitroimidazole, 5(4)-bromo-2-methyl-4(5)-nitroimidazole and 3-nitro-1,2,4-triazole to methyl acrylate as an acceptor was carried out. The optimisation process involved the use of an appropriate basic catalyst (DBU, DIPEA, NaOH, NaH, TEDA), a donor/base/acceptor ratio and the reaction temperature. The reactions were performed in DMF as solvent. Target Michael adducts were obtained in medium to excellent yields. Importantly, for imidazole and 1,2,4-triazole derivatives, no corresponding regioisomers were obtained.
Keywords: imidazole derivatives; methyl acrylate; Michael-type addition; pyrazole derivatives; 1,2,4-triazole derivatives